Studium instrumentów wartościowania kapitału intelektualnego organizacji - Pietruszka-Ortyl, Anna (The study of intellectual capitals measurement tools, 2006)
In the article the survey about different instruments of intellectual capital measurement is done. These tools are presented according to the convention - instruments that measure company's intellectual capital general level, tools that deals with the level of different elements of intellectual capital and the models of firm's intellectual capita diagnosis as the specific tools that are used by concrete organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 651-660